(untitled) (Ágora Journal, 2021)
In this article, we will analyze the internal dynamics of political communication between the governors-general of the State of Brazil and the municipal chambers. We will present the quantitative aspects of the exchanged correspondence between these institutions, highlighting the variations over time, as well as analyzing the subjects discussed to identify and characterize the dynamics of government established. We will focus on the correspondence of the general-government to the council of Salvador. We will seek to understand how these institutions formed bonds and how these relationships enabled the council of Salvador to exert influence in other captaincies and the governors-general to project their power on an Atlantic scale.